Answer:
8
I made a couple of assumptions so you might want to make sure I made the right assumptions.
I assumed you meant square root of z; not source of z.
I also assumed you meant x=2 not x=z.
Step-by-step explanation:
y varies directly with means y=k times something where k is a constant.
Inversely means to divide by whatever it says it varies inversely with.
So we have:
[tex]y=k \cdot \frac{x}{\sqrt{z}}[/tex]
We are given y=4 and x=2 and z=4, which means:
[tex]4=k \cdot \frac{2}{\sqrt{4}}[/tex]
[tex]4=k \cdot \frac{2}{2}[/tex]
[tex]4=k(1)[/tex]
[tex]4=k[/tex]
So the constant is k which means the equation for any (x,y,z) is:
[tex]y=4 \cdot \frac{x}{\sqrt{z}}[/tex]
We want to know y when x=6 and y=9:
[tex]y=4 \cdot \frac{6}{\sqrt{9}}[/tex]
[tex]y=4 \cdot \frac{6}{3}[/tex]
[tex]y=4 \cdot 2[/tex]
[tex]y=8[/tex]
multiply binomails (x + 2) (3x+1)
Answer:
The answer is 3x^2+7x+2
Step-by-step explanation:
Multiply each term of the second bracket with the first bracket.
We can write:
(x+2)(3x+1)= 3x(x+2)+1(x+2)
By multiplying the terms we get:
=3x^2+6x+x+2
Now simplify by combining like terms:
=3x^2+7x+2
Thus the answer is 3x^2+7x+2....
Answer:
3x² + 7x + 2
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor, that is
x(3x + 1) + 2(3x + 1) ← distribute both parenthesis
= 3x² + x + 6x + 2 ← collect like terms
= 3x² + 7x + 2
What is the solution to 2x^2+8x=x2-16? x=4, x=-2, x=2, x=4
Answer:
x=-4
Step-by-step explanation:
Given:
2x^2+8x=x2-16
2x^2-x^2+8x+16=0
x^2+8x+16=0
As per the formula (a+b)^2= a^2 +2ab +b^2
x^2+2(4)x+(4)^2=0
(x+4)^2=0
x+4=0
x=-4!
Answer:
x=-4
Step-by-step explanation:
Hello,
thanks for leaving your query here in brainly. I think I can help you with this
[tex]2x^{2} +8x=x^{2} -16\\organizing\ the\ terms\\2x^{2} +8x-x^{2}+16=0\\x^{2}+8x+16=0\\[/tex]
this can be factorized as
[tex]x^{2}+8x+16\\a^{2} +2ab+b^{2}=(a+b)^{2}\\ x^{2}+8x+16=(x+4)^{2}[/tex]
hence
[tex](x+4)^{2}=0\\now, isolate\ x\\\\\sqrt[]{(x+4)^{2}} =\sqrt{0}\\ x+4=0\\x=-4\\[/tex]
I hope it helps, Have a nice day.
Is the following relation a function?
Tamo
Yes
No
Which number sentence below matches this word problem?
George, the ginger cat, weighs 14 pounds. His pal, Igor, weighs 6 pounds.
How much more does George weigh than Igor?
A. 6* 14 = 20
OOO
O B. 84 = 14 = 6
O C. 14-6 = 8
O D. 14-8 = 6
SUBMIT
Answer:
The correct answer is option C.
Step-by-step explanation:
Weight of George = 14 pounds
Weight of Igor = 6 pounds
Difference between weight of cats :
= 14 pounds - 6 pounds = 8 pounds
This means that George is 8 pounds more in weight than Igor.
13x + 3y = 15 and y = 5 - 4x.
A. x = 0, y = 5
B. x = 5, y = 0
C. x = 9, y = -31
Pleaseee explain with words and number pleasee thank you so much
A. X=0 Y=5
Those 2 equations are a system. You answer is the value of x and y.
13x+3y=15
y=5-4x
First, lets make each equation fit into y=mx+b
13x +3y=15 y=5-4x
-13x -13x y=-4x+5
3y= -13x +15
Let's use the elimination method to solve this.
y= -4x+ 5 multiply top by 3
3y=-13x+15
3y=-12x+15
3y=-13x+15 subtract the equations
0=x
Lets use the x we just found to solve for y.
y=4x+5
y=4(0)+5
y=5
A rectangular solid object is 3 in. high, 6 in. long and 2 in. wide. What is its volume?
Answer:
The volume is 36 inches cubed.
Step-by-step explanation:
The volume of a rectangular prism is W*L*H.
You are given the H=3i, W=2 in, and L=6 in.
So now we plug into our formula for the volume of a rectangular prism which will result in 2*6*3=12*3=36.
The volume is 36 inches cubed.
Answer: [tex]36\ in^3[/tex]
Step-by-step explanation:
The volume of a rectangular prism can be calculated with this formula:
[tex]V=lwh[/tex]
Where "l" is the lenght, "w" is the width and "h" is the height.
In this case we know that this rectangular solid is 3 inches high, 6 inches long and 2 inches wide. Then:
[tex]h=3\ in\\l=6\ in\\w=2\ in[/tex]
Then, substituting these values into the formula, we get that its volume is:
[tex]V=(6\ in)(2\ in)(3\ in)\\\\V=36\ in^3[/tex]
Imagine each letter of the word “Mathematical” is written on individual pieces of paper and placed in a bag. Should you pick a random letter from that bag, what is the probability that you pick a vowel?
In the word "Mathematical"
Vowels are "a", "e", "a", "i", "a" from left to right
Consonants are "m", "t", "h", "m", "t", "c", "l"
5 vowels and 7 consonants of total 12 letters
So the probability of picking a vowel is
[tex] \frac{5}{12} [/tex]
Answer:
The probability to pick a vowel is [tex]\frac{5}{12} }[/tex]
Step-by-step explanation:
Probability = Required outcome / All possible outcome
From the question;
the word “Mathematical” is written on individual pieces of paper
We have to count the total numbers of letter present in the word
When we count properly, we have 12 total numbers of letters
The we proceed to count the numbers of vowel
Here are the vowel in the word “Mathematical” :
a, e, a, i, a
The vowels are 5 letters
Probability = Required outcome / All possible outcome
Required outcome = 5
All possible outcome = 12
Probability = [tex]\frac{5}{12} }[/tex]
The probability that you pick a vowel is [tex]\frac{5}{12} }[/tex]
Why did I get different answers to find x?
The first one I used Soh Cah Toa and the second one I used laws of sines
[tex]\bf tan(39^o)=\cfrac{\stackrel{opposite}{x}}{\stackrel{adjacent}{8}}\implies 8\cdot tan(39^o)=x\implies 6.48\approx x \\\\[-0.35em] ~\dotfill\\\\ \cfrac{sin(39^o)}{x}=\cfrac{sin(51^o)}{8}\implies \cfrac{8\cdot sin(39^o)}{sin(51^o)}=x\implies 6.48\approx x[/tex]
one thing to bear in mind is that calculators have two modes, Degree mode and Radian mode, if your calculator is in Radian mode and you plug in tan(39), it thinks "tangent of 39 radians" and so it gives that, bearing in mind that 1 radian is about 57°.
So make if you're using degrees as the angle, make sure your calculator is in Degree mode first, thus tan(39) will mean "tangent of 39 degrees".
[tex]\bf 8\cdot tan(39~rad) \approx 28.9~\hspace{10em} \cfrac{8\cdot sin(39~rad)}{sin(51~rad)}\approx 11.5[/tex]
Writing an equation of a line given its slope and y-intercept
Write an equation in slope-intercept form for the line with slope -3 and y-intercept 4.
Slope intercept form is [tex]y=mx+b \to y=-3x+4[/tex]
Answer:
y=-3x+4
Step-by-step explanation:
Slope-intercept form is y=mx+b
where m is the slope and b is the y-intercept.
m=-3 because -3 is the slope.
b=4 because 4 is the y-intercept.
Let's plug that into y=mx+b giving us y=-3x+4.
PLZ HELP!!! WILL GIVE BRAINLIEST
Paul wants to visit his aunt who lives 300 miles away from his house. He drives his car at about 50 miles/hour. If x represents the time spent driving and y represents the distance from his aunt’s house, which scatter plot could represent this situation?
The solution is, It would take 6 hours, to visit his aunt who lives.
What is speed?
Speed is measured as distance moved over time. The formula for speed is speed = distance ÷ time. To work out what the units are for speed, you need to know the units for distance and time. In this example, distance is in metres (m) and time is in seconds (s), so the units will be in metres per second (m/s).
Speed = Distance/ Time.
here, we have,
given that,
Paul wants to visit his aunt who lives 300 miles away from his house. He drives his car at about 50 miles/hour.
If x represents the time spent driving.
then, we get,
An equation for that could be:
50x = 300 (X is how long it would take)
So, 50 mph• X (time spent) = 300 miles
now, we have,
50x = 300
or, x = 300/50
or, x = 6
Hence, The solution is, It would take 6 hours, to visit his aunt who lives.
To learn more on speed click:
brainly.com/question/28224010
#SPJ3
Do you guys know the answer for number 3
Answer:
G
Step-by-step explanation:
solve the inequality x +1 > 18
Answer:
x > 17
Step-by-step explanation:
Given
x + 1 > 18 ( isolate x on the left by subtracting 1 from both sides )
x > 17
Answer:
x > 17
Step-by-step explanation:
x +1 > 18
Subtract 1 from each side
x +1 -1> 18-1
x > 17
What is solution to this inequality -13x>-39
Answer:
(-inf, 3)
Step-by-step explanation:
-13x > - 39
Multiply by -1/13, and flip the inequality.
x < 3
Answer:
[tex]\huge\boxed{x<3}[/tex]
Step-by-step explanation:
Multiply -1 both sides.
[tex]\displaystyle (-13x)(-1)<-39(-1)[/tex]
Solve.
[tex]\displaystyle 13x<39[/tex]
Divide by 13 both sides.
[tex]\displaystyle\frac{13x}{13}<\frac{39}{13}[/tex]
Simplify, to find the answer.
[tex]\displaystyle 39\div13=3[/tex]
[tex]\displaystyle x<3[/tex], which is our answer.
2 Points
What is the sum of the measures of the interior angles of a 14-sided polygon?
Answer:
2160°
Step-by-step explanation:
The sum of the interior angles of a polygon is
sum = 180° (n - 2) ← n is the number of sides
Here n = 14, hence
sum = 180° × 12 = 2160°
what are the real number solutions for x^2-3x+8=0
Answer:
There is no real solutions
Step-by-step explanation:
We have to count delta:
∆=(-3)²-4*8*1=-23.
Because ∆ is less than zero, your equation has only 2 imaginary solutions.
This equation hasn't got any real solutions (because √∆ isn't real)
Answer:
There are 0 real number solutions.
Step-by-step explanation:
You can use the discriminant to find the number of real number solutions.
The discriminant equation is:
[tex] {b}^{2} - 4ac[/tex].
a=1
b=-3
c=8
If the discriminant is positive, there are 2 real number solutions. If the discriminant is negative, there are 0 real number solutions. If the discriminant is 0, there is 1 real number solution.
[tex] {( - 3)}^{2} - 4(1)(8)[/tex]
= 9 - 32
= -23
The discriminant is negative.
0 real number solutions.
If abc~def which congruences are true by CPCTC?
Answer:
The correct options are A and B.
Step-by-step explanation:
Given information: ΔABC≅DEF
Corresponding parts of congruent triangle are congruent (CPCTC).
The corresponding angles of both triangles are congruent.
[tex]\angle A\cong \angle D[/tex]
[tex]\angle B\cong \angle E[/tex]
[tex]\angle C\cong \angle F[/tex]
The corresponding side of both triangles are congruent.
[tex]\angle AB\cong \angle DE[/tex]
[tex]\angle BC\cong \angle EF[/tex]
[tex]\angle AC\cong \angle DF[/tex]
Therefore the correct options are A and B.
The congruencies that are true are;
A. [tex]\overline{AB}[/tex] ≅ [tex]\overline{DE}[/tex], and B. ∠C ≅ ∠F
The reason the selected options are correct is given as follows;
Known parameter;
ΔABC ≅ ΔDEF (Change of ~ to ≅ based on complete question accompanying screen grab as posted online)
CPCTC is the acronym for Congruent Parts of Congruent Triangles are Congruent
Required: To select the congruences that are true
Solution:
By observation, the height of ΔABC is equal to the height of ΔDEF, therefore;
[tex]\overline{AB}[/tex] ≅ [tex]\overline{DE}[/tex]∠C and ∠F are angles located in corresponding parts of both triangles
∴ ∠C ≅ ∠FWhile the other options; ∠E and ∠C, ∠A and ∠E, [tex]\overline{AB}[/tex] and [tex]\overline{DF}[/tex], and [tex]\overline{AC}[/tex] and [tex]\overline{DE}[/tex] are not corresponding parts and they are therefore not congruent
The congruencies that are true are; A. [tex]\overline{AB}[/tex] ≅ [tex]\overline{DE}[/tex], and B. ∠C ≅ ∠F
Learn more about CPCTC here:
https://brainly.com/question/1805755
what property does the following expression demonstrate? -10+6=6+(-10)
ANSWER
Commutative property of addition.
EXPLANATION
Let a,b be real numbers. The commutative property of addition states that,
[tex]a + b = b + a[/tex]
If we let a=-10 and b=6, then
[tex]-10+6=6+(-10)[/tex]
Therefore the given expression demonstrates the commutative property of addition.
The commutative property of addition tells us that, the order in which we add two real numbers does not affect the result.
Charlie divided 15 cents among
four small bags.
He can use the four bags to pay any
amount between 1 cent and 15 cents, Bag without opening them.
How many cents did Charlie put in each bag?
Answer:0.035
Step-by-step explanation:
I used a calculator and put in 15 / 4 and got 0.035
Charlie should divide the 15 cents into four bags with 1 cent, 2 cents, 4 cents, and 7 cents respectively. Using combinations of these bags, he can pay any amount between 1 cent and 15 cents without opening them.
Explanation:The question asks us to figure out how Charlie can divide 15 cents among four small bags so he can use these bags to pay any amount between 1 cent and 15 cents without opening them.
To solve this, we need to think about the binary representation of numbers, because each bag can either be used or not used in each transaction, similar to how a binary '1' or '0' can represent 'on' or 'off'.
Therefore, he should put the amounts that correspond to the powers of 2 in three of the bags: 1 cent, 2 cents, and 4 cents, and in the last bag, we put the sum of these three, which is 7 cents.
This way, he can make any amount up to 15 cents:
1 cent: Use the 1-cent bag.2 cents: Use the 2-cent bag.3 cents: Use the 1-cent and 2-cent bags.4 cents: Use the 4-cent bag.5 cents: Use the 1-cent and 4-cent bags.6 cents: Use the 2-cent and 4-cent bags.7 cents: Use the 1-cent, 2-cent, and 4-cent bags.8 cents: Use the 7-cent bag.9 cents: Use the 1-cent and 7-cent bags.10 cents: Use the 2-cent and 7-cent bags.11 cents: Use the 1-cent, 2-cent, and 7-cent bags.12 cents: Use the 4-cent and 7-cent bags.13 cents: Use the 1-cent, 4-cent, and 7-cent bags.14 cents: Use the 2-cent, 4-cent, and 7-cent bags.15 cents: Use all four bags.Type the correct answer in the box. Write the simplified form of -62^1/3
Answer: [tex]\sqrt[3]{-62}[/tex]
Step-by-step explanation:
It is important to remember the following:
[tex]a^{(\frac{1}{n})=\sqrt[n]{a}[/tex]
In this case we have:
[tex]-62^{\frac{1}{3}[/tex]
Then, in order to simplify it, we need to rewrite it in radical form, where the index of the root will be 3 and the radicand will be -62.
Therefore, the simplified form is this:
[tex]-62^{\frac{1}{3}}=\sqrt[3]{-62}[/tex]
Answer: -4
Step-by-step explanation: I put it in Desmos calc.
Add the equations.
2x-3y = -1
+ 3x + 3y= 26
Answer:
The answer in the procedure
Step-by-step explanation:
we have
2x-3y=-1 ----> equation A
3x+3y=26 --> equation B
Solve the system by elimination
Adds equation A and equation B
2x-3y=-1
3x+3y=26
----------------
2x+3x=-1+26
5x=25
x=25/5
x=5
Find the value of y
substitute the value of x in equation A or equation B and solve for y
2(5)-3y=-1
10-3y=-1
3y=10+1
y=11/3
Answer:
5x=25
Step-by-step explanation:
A p e x
multiply (3x^2-2x)(2x^2+3x-1)
Answer:
[tex]\large\boxed{(3x^2-2x)(2x^2+3x-1)==6x^4+5x^3-8x^2+2x}[/tex]
Step-by-step explanation:
Use the distributive property and [tex](a^n)(a^m=)=a^{n+m}[/tex]
[tex](3x^2-2x)(2x^2+3x-1)\\\\=(3x^2)(2x^2)+(3x^2)(3x)+(3x^2)(-1)+(-2x)(2x^2)+(-2x)(3x)+(-2x)(-1)\\\\=6x^4+9x^3-3x^2-4x^3-6x^2+2x\qquad\text{combine like terms}\\\\=6x^4+(9x^3-4x^3)+(-3x^2-5x^2)+2x\\\\=6x^4+5x^3-8x^2+2x[/tex]
multiplication of (3x^2-2x)(2x^2+3x-1) is 6X⁴+5X³-9x²+2X
What are polynomials?A polynomial expression is an expression that can be built from constants and symbols.Polynomials are algebraic expressions that comprise exponents which can be added, subtracted, or multiplied. Polynomials are of different types. Monomial- Linear equations (A monomial is a polynomial with one term)Binomia- quadratic equation (A binomial is a polynomial with two, unlike terms).CALCULATION:-
⇒(3X²-2X)(2X²+3X-1)
⇒6X⁴+9X³-3X²-4X³-6X²+2X
⇒ 6X⁴+5X³-9x²+2X (answer)
Learn more about polynomials here:-https://brainly.com/question/2833285
#SPJ2
What is the surface area of the triangular prism?
4 feet
5 feet
20 feet
3 feet
Hurry plzz
Answer: 252
Step-by-step explanation:
A triangular prism has three rectangular sides and two triangular faces. To find the area of the rectangular sides, use the formula A = lw, where A = area, l = length, and h = height. To find the area of the triangular faces, use the formula A = 1/2bh, where A = area, b = base, and h = height.
HELP ASAP!!! Whats the answer to the last one?
What is the average rate of change from x=10 to x=15?
Answer:
-2
Step-by-step explanation:
The rate of change is
roc = f(x2) - f(x1)
---------------
x2 -x1
x2 is the last point or 15
x1 is the first point or 10
f(15) = 10 from the graph
f(10) = 20 from the graph
roc = f(15) - f(10)
---------------
15-10
roc = 10 - 20
---------------
15-10
roc = -10
--------
5
roc = -2
Find the area of the regular polygon round to the nearest tenth
bearing in mind that a diagonal line from the center of a square will give us an isosceles triangle, Check the picture below.
Answer:
The area of this polygon is 98.1 yd²
Step-by-step explanation:
Check the image below.
The diagonal line from the corner of a square to the center of this one will shape an isosceles triangle.
The Pythagoras theorem give us the following formula:
A² + A² = H²
Both "A" are the sides and H is the hypotenuse, seeing the figure, the diagonal coincide with the hypotenuse and the measure is 7 yd.
A² + A² = 72
2A² = 49
A²= 49/2
A²= 24. 5
A=√24.5
A= 4.95 yd
Knowing that the diagonal ends up in the center of the square, we assume that the side of the triangle (“A” side) is the half of the side of the square, then this last one is 2A. Bearing in mind that square have all of the sides with the same measure, the four sides have a 2A size.
2A = 2(4.95) =9.9 yd
Each side of the square measures 9.9 yd
The area of a square is
Side²= (2A)2²
(9.9)²= 98.1 yd²
The area of this polygon is 98.1 yd²
15
Ellen is currently twice as old as Maria, but in
6 years, Maria will be 2/3 as old as Ellen. How old is
Ellen now?
16
If 2x - 2y = 5 and x + y = 6, what is the value
How do I do this?
Answer:
15) Ellen is 12 years old.
16) Don't know what value you are looking for but x=(17/4) while y=(7/4) since the set of equations is 2x-2y=5 and x+y=6.
Step-by-step explanation:
15) Ellen (E) is currently twice as old as Maria (M).
Twice means to multiply by 2.
E=2M is therefore the equation for this part of the problem.
In 6 years, Maria (M) will be 2/3 as old as Ellen (E). Keep in my Maria as aged 6 years (M+6) and Ellen as aged 6 years (E+6):
M+6=(2/3)(E+6).
So we have this system to solve:
E=2M
M+6=(2/3)(E+6).
I'm going to replace the E in the second equation with 2M since the first equation says E=2M:
M+6=(2/3)(E+6) with E=2M:
M+6=(2/3)(2M+6)
Distribute:
M+6=(4/3)M+(12/3)
Reducing 12/3 to 4:
M+6=(4/3)M+4
Subtract 4 on both sides:
M+2=(4/3)M
Subtract M on both sides:
2=(4/3)M-M
Find a common denominator:
2=(4/3)M-(3/3)M
Combine like terms:
2=(1/3)M
Multiply both sides by the reciprocal of 1/3 which is 3:
3(2)=3(1/3)M
6=1M
6=M
M=6
Maria is six years old.
Recall E=2M.
So if M=6, then E=2(6)=12.
So currently E is twice as old as M since 6(2)=12.
In six years, M will be 12 which E will be 18.
M (12) is two-thirds as old as E (18) since 12=2/3(18)
16)
2x-2y=5
x + y=6
Your question doesn't state which value it is looking for.
Anyways I'm going to solve the system for the point (x,y) and then you can decide which part of this answer to use.
I'm going to solve this system by elimination. Each equation already has the same form: ax+by=c. I just need a column with the variables to be opposite or the same.
I'm going to multiply both sides of equation 2 by 2:
2x-2y=5
2x+2y=12
Now I have opposites in a column: -2y and 2y.
When you add opposites you get 0 so this is what you want to use elimination.
We are going to add the equations now:
2x-2y=5
2x+2y=12
------------------Adding!
4x+0y=17
4x =17
Divide both sides by 4:
x =17/4
Now if x=17/4 and x+y=6, then we have that (17/4)+y=6.
Subtracting 17/4 on both sides gives us y=6-(17/4).
Finding a common denominaotr gives us y=(24/4)-(17/4).
Simplifying this gives us y=(7/4).
The point of intersection (the solution) is (17/4 , 7/4)
The question is about solving two mathematical problems. The first problem is about ages, where Ellen is found to be 12 years old and Maria is six years old. The second problem is solving a linear equation system where the solution is x = 5 and y = 1.
Explanation:
Let's denote Maria's age as X and Ellen's age as Y. According to the problem, Ellen is twice as old as Maria, so that we can write Y = 2X. Maria will be 2/3 as old as Ellen in six years, so we can write another equation as X + 6 = 2/3 * (Y + 6). Now, we solve these equations. Substituting Y = 2X into the second equation, we get X + 6 = 2/3 * (2X + 6). Solving this, we find X = 6, so Maria is 6. Substituting X = 6 into Y = 2X, we find Y = 12, so Ellen is 12 years old.
For the second part of the problem, we solve the system of equations 2x - 2y = 5 and x + y = 6. One way is to take the second equation and solve for x: x = 6 - y. Substituting this into the first equation, we get 2*(6-y) - 2y = 5. Solving this simplifies to y = 1. Then, covering y = 1 into x + y = 6, we find x = 5.
Learn more about Solving Equations here:https://brainly.com/question/29050831
#SPJ3
Figure ABCD is rotated clockwise about the origin through 90°. Identify the coordinates for the given figure after 90° rotation about the origin.
Answer:
D[3, 3], C[1, 4], B[0, 1], A[4, -1]
Step-by-step explanation:
Whenever you are doing a 90° clockwise rotation ABOUT THE ORIGIN, it is in the form of [y, -x], meaning you take the y and make it your x, then take your original x and put its OPPOSITE.
90° counterclockwise rotation → [-y, x]
90° clockwise rotation → [y, -x]
I hope this helps, and as always, I am joyous to assist anyone at any time.
Find the coordinates of the midpoint of a segment having the given endpoints.
Q(-0.4, 2.5), R(3.5, 1.5)
of
Select one:
0
O
a. (1.55, 2)
b. (1.05, 2.5)
C. (-1.95, 0.5)
d. (-3.9, 1)
O
Answer:
A. (1.55, 2)
Step-by-step explanation:
The formula to apply when finding the midpoint of a segment where the coordinates of the end points are given is;
[tex]midpoint=(\frac{x_1+x_2}{2} ,\frac{y_1+y_2}{2} )[/tex]
where (x₁,y₁) and (x₂,y₂) are the coordinates of the end points
Given;
x₁= -0.4 ,y₁=2.5, x₂=3.5, y₂=1.5 then applying the formula for midpoint
[tex]=(\frac{-0.4+3.5}{2} ,\frac{2.5+1.5}{2} )\\\\\\=(\frac{3.1}{2} ,\frac{4.0}{2} )\\\\\\=(1.55,2.0)[/tex]
What is the volume of the sphere shown below? R=12
Answer:
2304
Step-by-step explanation:
The volume of the sphere is 2304π cubic units or 7238.229 cubic units if the radius is 12 units.
What is a sphere?It is defined as three-dimensional geometry when half-circle two-dimensional geometry is revolved around the diameter of the sphere that will form.
[tex]\rm V = \dfrac{4}{3} \pi r^3[/tex]
We have a radius of the sphere R = 12 units
Volume:
[tex]\rm V = \dfrac{4}{3} \pi (12)^3[/tex]
V = 2304π cubic units or
V = 7238.229 cubic units
Thus, the volume of the sphere is 2304π cubic units or 7238.229 cubic units if the radius is 12 units.
Learn more about the sphere here:
brainly.com/question/11374994
#SPJ2
In the figure, ACHF = AEHD. Which statement is true by CPCTC
DH HF
FA HE
GH HD
GF HD
Answer:
DH and HF correspond.
Step-by-step explanation:
The order matters in a congruence statement.
You are given Figure GHF=Figure EHD.
I say the order matters in a congruence statement because it tells you the parts that correspond.
Angles G and E correspond because they are both first.
Angles H and H correspond because they are both second.
Angles F and D correspond because they are both third.
The same thing works with the segments.
Segments GH and EH correspond because it goes first to second for both.
Segments HF and HD correspond because it goes second to third for both.
Segments FG and DE correspond because it goes third back to first for both.
I have named all the correspond parts for you congruence statement:
Figure GHF=Figure EHD.
So let's look at the choices.
DH and HF correspond.
Answer:
DH and HF correspond.
Step-by-step explanation:
Simplify square root of 300x8/ 27x12
Answer:
10
-------------
3x^2
Step-by-step explanation:
First lets simplify what is inside the square root
300x8
---------------
27x12
3 * 100 x^8
------------------
3 *9 x^12
The 3's cancel and we know a^b/ a^c = a^(b-c)
100/9 x^ (8-12)
100/9 x^-4
sqrt( 100/9 x^-4)
Put the negative exponent in the denominator and make it positive
sqrt( 100 / (9x^4) )
We know that sqrt( a / b) = sqrt(a) / sqrt( b)
sqrt(100)
----------------
sqrt( 9x^4)
10
-------------
3x^2